Preparation method and application of calcium carbonate biomineralized coated Prussian blue lipid nanoparticles
By loading calcium carbonate on mesoporous Prussian blue and preparing a lipid layer, the problems of poor water solubility and limited drug-loading capacity of calcium-based nanomaterials are solved, and the acidity and hypoxia of the tumor microenvironment are efficiently regulated, thereby enhancing calcium-loading efficiency and biocompatibility.
Patent Information
- Application Number
- CN202411993141.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing calcium-based nanomaterials have poor water solubility, limited drug loading capacity, and insufficient calcium content in the tumor microenvironment to effectively regulate acidity and hypoxic environment.
By loading calcium carbonate on mesoporous Prussian blue and preparing a lipid layer on the surface, calcium carbonate biomineralization coated Prussian blue lipid nanoparticles are prepared, which improves the drug loading and calcium loading efficiency.
It achieves efficient dual regulation of the acidity and hypoxia of the tumor microenvironment, destroys the calcium homeostasis in the cell, enhances the dispersion and stability of nanoparticles, and improves biocompatibility.
Smart Images

Figure CN119745831A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical materials, and particularly relates to a preparation method and application of calcium carbonate biomineralized Prussian blue lipid-coated nanoparticles. Background Art
[0002] Due to the complexity and high heterogeneity of the tumor microenvironment, as well as the problems of combination timing, dose optimization, increased toxicity, and enhanced side effects in combined tumor therapy, it is still challenging to develop specific combination schemes based on the characteristics of the tumor microenvironment to achieve efficient remodeling of the tumor microenvironment and better combinations of drugs. A large number of studies have shown that long-term slightly acidic and hypoxic environments in the tumor microenvironment can promote tumor growth, invasion and metastasis, and also affect the functions of various immune cells. The chemical properties of biomaterials can be "customized" based on the characteristics of the tumor microenvironment and are widely used in the biomedicine field. Therefore, using the unique advantages of biomaterials to specifically dually regulate the acidity / hypoxia tumor microenvironment is expected to provide favorable conditions for further multi-effect synergistic and integrated inhibition of tumor growth.
[0003] Currently, a variety of biomaterial-based strategies have been explored to regulate the acidity and hypoxia in the tumor microenvironment. Among them, calcium-based nanomaterials, mainly including calcium carbonate, calcium phosphate, calcium peroxide, etc., can responsively release Ca in the acidic tumor microenvironment. 2+ , consumes H of acidic substances inside and outside tumor cells + , has a strong acidity buffering function; and its own good biocompatibility, biodegradability, easy modification and other characteristics have attracted widespread attention in anti-tumor treatment. In addition, Ca 2+ As the most abundant metal element in the human body, it is a new type of tumor immunogenic cell death inducer with both efficacy and biosafety. Therefore, the development of functionalized calcium-based nanomaterials for cellular calcium overload has gradually become a research hotspot. However, calcium-based nanomaterials have poor water solubility and, compared with other polymer materials, have limited drug delivery capabilities as nanodelivery platforms. The construction of hollow calcium-based materials can greatly enhance drug loading capacity, but the reduction of calcium content in the material will directly affect its acidity buffering function in the tumor microenvironment.
[0004] Prussian blue is a 2+ and Fe 3+The organic metal framework structure, composed of cyano groups, has a catalase-like activity that catalyzes oxygen production and is widely used to regulate hypoxia in the tumor microenvironment. Compared to inorganic nanoenzyme materials such as manganese dioxide, platinum, ruthenium, and cerium, Prussian blue is size-controlled, easily modifiable, and exhibits excellent biocompatibility. Therefore, it is widely used to improve the hypoxic tumor microenvironment, treat various inflammatory diseases, and act as an antidote for certain radioactive heavy metal poisoning. However, Prussian blue has poor dispersibility in aqueous solutions, requiring surface modification. Summary of the Invention
[0005] To solve the above-mentioned technical problems, the purpose of the present invention is to provide a method for preparing calcium carbonate biomineralized Prussian blue lipid nanoparticles to solve the problems of poor water solubility and low calcium content of calcium-based nanomaterials in the prior art. The calcium carbonate biomineralized Prussian blue lipid nanoparticles are prepared by loading calcium carbonate on mesoporous Prussian blue and then preparing a lipid layer on the surface. The drug loading capacity of the prepared nanoparticles is greatly improved and they have sufficient calcium loading efficiency, thereby achieving the purpose of efficiently dual-regulating the acidity / hypoxia tumor microenvironment and disrupting intracellular calcium homeostasis.
[0006] To achieve the above-mentioned purpose, the present invention first provides a preparation method of calcium carbonate biomineralized Prussian blue lipid nanoparticles. The preparation method uses potassium ferrocyanide and polyvinylpyrrolidone K30 as raw materials, prepares mesoporous Prussian blue nanoparticles by hydrothermal synthesis and hydrochloric acid etching, and then uniformly coats the surface of the mesoporous Prussian blue by gas diffusion based on biomineralization; finally, a lipid layer is modified on the surface of the shell-core structure of the calcium carbonate coated mesoporous Prussian blue by an emulsified solvent volatilization method.
[0007] A method for preparing calcium carbonate biomineralized Prussian blue lipid-coated nanoparticles comprises the following steps:
[0008] (1) Potassium ferrocyanide and polyvinylpyrrolidone were dissolved in a hydrochloric acid solution and stirred at room temperature to obtain a clear yellow solution; the yellow solution was transferred to a reactor and heated at 80°C for 24 hours. After the reaction was completed, the obtained dark blue liquid was centrifuged at high speed, the supernatant was discarded, and the precipitate was washed with deionized water several times and freeze-dried to obtain Prussian blue nanoparticles;
[0009] (2) The Prussian blue nanoparticles obtained in step (1) and polyvinyl pyrrolidone were dissolved in a hydrochloric acid solution, stirred at room temperature for 3 h, and then the mixed solution was transferred to a reactor and heated at a constant temperature of 140° C. for 3 h; after the reaction was completed, the obtained dark blue liquid was centrifuged at high speed, the supernatant was discarded, and the precipitate was washed with deionized water several times, and freeze-dried to obtain mesoporous Prussian blue nanoparticles;
[0010] (3) taking the mesoporous Prussian blue nanoparticles obtained in step (2), dissolving the mesoporous Prussian blue nanoparticles, calcium chloride and polyvinyl pyrrolidone in an organic solvent and placing the mixture in a beaker; wrapping the beaker with tin foil, piercing the beaker, and placing the beaker and dry ammonium bicarbonate in a constant temperature box at 45° C. for 12 hours. After the reaction is completed, centrifuging at high speed, discarding the supernatant, washing the precipitate with an organic solvent, and centrifuging at low speed to remove large particles in the system. The mixture is freeze-dried to obtain calcium carbonate-coated mesoporous Prussian blue nanoparticles;
[0011] (4) Phosphatidylcholine, cholesterol, and distearoylphosphatidylethanolamine-polyethylene glycol are dissolved in a mixed organic solvent to prepare liquid A; the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in step (3) are dispersed in deionized water to prepare liquid B; liquid A and liquid B are mixed in a volume ratio of 1:5, intermittently ultrasonicated with an ice bath to form an oil-in-water emulsion, and the organic solvent is removed by rotary evaporation. The calcium carbonate biomineralized-coated Prussian blue lipid nanoparticles are filtered through an organic filter membrane to obtain the nanoparticles.
[0012] In one embodiment of the present invention, in step (1), the concentration of the hydrochloric acid solution is 0.1-1M.
[0013] In one embodiment of the present invention, in step (1), the mass concentration of potassium ferrocyanide in the yellow solution is 0.006-0.06 g / mL, and the mass concentration of polyvinyl pyrrolidone is 0.075-0.75 g / mL.
[0014] In one embodiment of the present invention, in step (1), the rotation speed during high-speed centrifugation is 15,000-40,000 rpm, and the centrifugation time is 0.25-1 h.
[0015] In one embodiment of the present invention, in step (1), the freeze-drying temperature is -80°C and the time is 24-48 hours.
[0016] In one embodiment of the present invention, in step (2), the concentration of the hydrochloric acid solution is 1-2M.
[0017] In one embodiment of the present invention, in step (2), the mass concentration of Prussian blue nanoparticles in the mixed solution is 0.1-1 mg / mL, and the mass concentration of polyvinyl pyrrolidone is 1-5 mg / mL.
[0018] In one embodiment of the present invention, in step (2), the rotation speed during high-speed centrifugation is 15,000-40,000 rpm, and the centrifugation time is 0.25-1 h.
[0019] In one embodiment of the present invention, in step (2), the freeze-drying temperature is -80°C and the time is 24-48 hours.
[0020] In one embodiment of the present invention, in step (3), the organic solvent includes ethanol and / or methanol.
[0021] In one embodiment of the present invention, in step (3), the mass ratio of the mesoporous Prussian blue nanoparticles, calcium chloride and polyvinyl pyrrolidone is 1:32-72:700.
[0022] In one embodiment of the present invention, in step (3), the amount of ammonium bicarbonate used is 1-5 g.
[0023] In one embodiment of the present invention, in step (3), the rotation speed during high-speed centrifugation is 15,000-40,000 rpm, and the centrifugation time is 0.25-1 h.
[0024] In one embodiment of the present invention, in step (3), the rotation speed during low-speed centrifugation is 3000-5000 rpm, and the centrifugation time is 5-15 min.
[0025] In one embodiment of the present invention, in step (3), the freeze-drying temperature is -80°C and the time is 24-48 hours.
[0026] In one embodiment of the present invention, in step (4), in the solution A, the mass ratio of lecithin, cholesterol, and distearoylphosphatidylethanolamine-polyethylene glycol in the mixed organic solvent is 2:1:1, and the concentration of the lecithin is 1-3 mg / mL.
[0027] In one embodiment of the present invention, in step (4), the mixed organic solvent is a mixed solvent of chloroform and / or dichloromethane and alcohol, the alcohol includes methanol and / or ethanol, and the mass ratio of the chloroform and / or dichloromethane to the alcohol is 2:1.
[0028] In one embodiment of the present invention, in step (4), the molecular weight of the distearoylphosphatidylethanolamine-polyethylene glycol is in the range of 2000-5000.
[0029] In one embodiment of the present invention, in step (4), the mass concentration of the calcium carbonate-coated mesoporous Prussian blue nanoparticles in the solution B is 1-5 mg / mL.
[0030] In one embodiment of the present invention, in step (4), the rotary evaporation temperature is 45-60° C., the organic filter membrane is cellulose diacetate, and the pore size is 0.45 μm.
[0031] The present invention also provides calcium carbonate biomineralization-coated Prussian blue lipid nanoparticles prepared according to the above preparation method.
[0032] The present invention also provides a use of the calcium carbonate biomineralized Prussian blue lipid-coated nanoparticles in the preparation of anti-tumor drugs.
[0033] Beneficial effects:
[0034] (1) In the nanoparticles prepared by the present invention, a calcium carbonate coating is formed on the surface of the mesoporous Prussian blue by a gas diffusion method based on biomineralization technology. The thickness and calcium loading of the calcium carbonate coating are regulated by controlling the ratio of the mesoporous Prussian blue to calcium chloride. The control process is simple and easy to operate.
[0035] (2) In the nanoparticles prepared by the present invention, the shell-core structure of calcium carbonate mineralized and coated with mesoporous Prussian blue greatly increases its drug loading capacity while having sufficient calcium loading efficiency to produce the effects of efficient dual regulation of acidity / hypoxia tumor microenvironment and disruption of intracellular calcium homeostasis.
[0036] (3) The nanoparticles prepared by the present invention adopt an emulsified solvent evaporation method to modify the surface of the core-shell structure of calcium carbonate mineralized and coated with mesoporous Prussian blue with lipids, which greatly increases the dispersibility and stability of the nanoparticles.
[0037] (4) The lipid nanoparticles prepared by the method of the present invention can efficiently adjust the pH under acidic conditions (pH 4.5), which will help regulate the acidity of the tumor microenvironment, making the environment unfavorable for tumor growth.
[0038] (5) The lipid nanoparticles prepared by the method of the present invention can efficiently generate dissolved oxygen under acidic conditions (pH 4.5), and the mesoporous Prussian blue in the nanoparticles can exert peroxidase-like activity, catalyzing H2O2 into O2 and H2O, which will help regulate hypoxia in the tumor microenvironment, making the environment unfavorable for tumor growth.
[0039] (6) The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared by the present invention can efficiently release Ca in acidic solution. 2+ , and Ca 2+ It can be efficiently deposited in MCF-7 / ADR cells to achieve the functions of acidity regulation in the tumor microenvironment and disrupting intracellular calcium ion homeostasis.
[0040] (7) In the nanoparticles prepared by the present invention, calcium and iron are both essential trace elements for the human body, and no other heavy metal ions are involved, which greatly improves the biocompatibility of the nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 These are electron micrographs of Prussian blue nanoparticles prepared by hydrothermal synthesis; a is a scanning electron micrograph; b is a transmission electron micrograph.
[0042] Figure 2Transmission electron microscopy image of mesoporous Prussian blue nanoparticles after hydrochloric acid etching.
[0043] Figure 3 This is a scanning electron micrograph of the core-shell structure of calcium carbonate mineralized and coated with mesoporous Prussian blue prepared in step 3 of Example 1.
[0044] Figure 4 These are electron micrographs of the calcium carbonate mineralized-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1; a is a scanning electron micrograph; and b is a transmission electron micrograph.
[0045] Figure 5 The acidity regulation ability of mesoporous Prussian blue lipid nanoparticles coated for calcium carbonate mineralization at pH 4.5 was investigated.
[0046] Figure 6 Investigation of the Oxygen Generation Capacity of Mesoporous Prussian Blue-coated Lipid Nanoparticles for Calcium Carbonate Mineralization
[0047] Figure 7 Investigation of the calcium release capacity of mesoporous Prussian blue-coated lipid nanoparticles for calcium carbonate mineralization.
[0048] Figure 8 Calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles for intracellular Ca 2+ Sedimentation investigation (blue: Hoechst 33258; green: Fluo-3 AM).
[0049] Figure 9 This is an investigation on ROS consumption in tumor cells induced by calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles; a is the PBS-administered group; b is the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles-administered group (blue: Hoechst 33258; green: DCFH-DA).
[0050] Figure 10 In vivo targeting investigation of calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles.
[0051] Figure 11 Scanning electron microscope image of the core-shell structure of mesoporous Prussian blue coated with calcium carbonate mineralization prepared with a mass ratio of mesoporous Prussian blue to calcium chloride of 1:72.
[0052] Figure 12 Liquid images of calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared by different preparation methods; a is the gas diffusion method; b is the chemical co-precipitation method.
[0053] Figure 13 Transmission electron microscopy image of calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared by chemical co-precipitation method. DETAILED DESCRIPTION
[0054] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it does not limit the scope of implementation of the present invention.
[0055] Example 1
[0056] A method for preparing calcium carbonate mineralized and coated mesoporous Prussian blue lipid nanoparticles comprises the following steps:
[0057] Step 1: Accurately weigh 7.5g of polyvinylpyrrolidone and 0.6g of potassium ferricyanide, respectively, and dissolve them in 100mL of 0.01M HCl solution. Stir at room temperature for 30 minutes to obtain a clear yellow solution. Transfer the solution to a reactor and heat at 80°C for 24 hours. After the reaction, centrifuge the resulting dark blue liquid at 40,000rpm for 15 minutes, discard the supernatant, wash the precipitate three times with deionized water, and freeze-dry to obtain Prussian blue nanoparticles.
[0058] Step 2: Accurately weigh 20 mg of the Prussian blue nanoparticles prepared in step 1 and disperse them in 20 mL of 1 M HCl solution. Add 100 mg of PVPK30 and stir magnetically at room temperature for 3 hours. Then transfer the solution to a reactor and heat at 140°C for 3 hours. After the reaction, centrifuge the obtained dark blue liquid at 40,000 rpm for 15 minutes, discard the supernatant, wash the precipitate with deionized water three times, and freeze-dry to obtain mesoporous Prussian blue nanoparticles.
[0059] Step 3: Dissolve 1 mg of the mesoporous Prussian blue nanoparticles obtained in Step 2 in 30 mL of anhydrous ethanol, 32 mg of calcium chloride, and 700 mg of polyvinylpyrrolidone K30. Place the mixture in a beaker. Wrap the beaker in tin foil, pierce the foil, and place the beaker and 5 g of dry ammonium bicarbonate in an incubator at 45°C for 12 hours. After the reaction, centrifuge at 40,000 rpm for 15 minutes, discard the supernatant, and wash the precipitate with anhydrous ethanol. Centrifuge at 5,000 rpm for 5 minutes to remove large particles. Freeze-dry the mixture to obtain calcium carbonate-coated mesoporous Prussian blue nanoparticles.
[0060] Step 4: Take 2 mg of lecithin, 1 mg of cholesterol and 1 mg of distearoylphosphatidylethanolamine-polyethylene glycol and dissolve them in 1 mL of a mixed solution of chloroform and methanol (volume ratio 2:1) to prepare liquid A; take 20 mg of calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in step 3 and disperse them in 5 mL of deionized water to prepare liquid B; mix liquid A and liquid B, and form an oil-in-water emulsion by intermittent probe ultrasound in an ice bath. Then, remove the organic solvent by rotary evaporation at 60°C, and filter with an organic filter membrane to obtain calcium carbonate biomineralized Prussian blue lipid nanoparticles.
[0061] The Prussian blue nanoparticles prepared in step 1 of Example 1 were examined by electron microscopy. Figure 1 Transmission electron microscopy and scanning electron microscopy images show that the prepared Prussian blue nanoparticles have a regular cubic structure and a particle size of about 100 nm.
[0062] The mesoporous Prussian blue nanoparticles prepared in step 2 of Example 1 were examined by electron microscopy. The experimental results are as follows: Figure 2 The experimental results show that the particle size of the mesoporous Prussian blue nanoparticles obtained after hydrochloric acid etching did not change significantly compared to before etching. The edges of the cubic structure became smooth due to the influence of hydrochloric acid etching, and pores of varying sizes were formed in the center of the nanoparticles.
[0063] The calcium carbonate coated mesoporous Prussian blue nanoparticles prepared in step 3 of Example 1 were examined by electron microscopy. The experimental results are as follows: Figure 3 The experimental results show that the cubic morphology of mesoporous Prussian blue can be seen in the calcium carbonate-coated mesoporous Prussian blue nanoparticles, and the surface is covered with a uniform CaCO3 coating.
[0064] The calcium carbonate coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 were examined by electron microscopy. The experimental results are as follows: Figure 4 The experimental results show that a lipid coating layer can be formed on the surface of calcium carbonate-coated mesoporous Prussian blue nanoparticles by the emulsification solvent evaporation method, and the prepared nanoparticles have a uniform particle size of about 130 nm.
[0065] The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 were tested for their ability to regulate acidity. The nanoparticles were dispersed in PBS solutions at pH 4.5 and pH 7.4, respectively, to a concentration of 0.1 mg / mL. The solution was stirred at 37°C for 0 h and 6 h. The pH of the solution was measured to examine the pH regulating ability of the blank carrier. The experimental results of the acidity regulating ability of calcium carbonate mineralized-coated mesoporous Prussian blue lipid nanoparticles at pH 4.5 are shown in Figure 2. Figure 5 As shown. Figure 5 As can be seen from the results, the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 can effectively adjust the pH in an acidic solution (pH 4.5). This is because the calcium carbonate coating releases calcium ions under acidic conditions and consumes hydrogen protons under acidic conditions, resulting in a better adjustment ability. However, in a neutral solution (pH 7.4), due to the poor calcium ion release ability and low hydrogen proton concentration, the ability of the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles to increase pH is not significant.
[0066] The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 were tested for their oxygen generation capacity. The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles were added to a 10 mM H2O2 solution to a nanoparticle concentration of 0.1 mg / mL. A dissolved oxygen meter was used to monitor the dissolved oxygen concentration of the mixed solution before and after the addition of the nanoparticles to test the oxygen generation capacity of the nanoparticles. The experimental results are shown in Figure 2. Figure 6 The experimental results show that the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 have an insignificant ability to generate oxygen in a neutral solution (pH 7.4), but can efficiently generate oxygen in an acidic solution (pH 4.5).
[0067] The calcium release capacity of the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 was investigated. The nanoparticles were dispersed in PBS aqueous solutions with different pH values (7.4, 6.8, or 4.5) to a concentration of 1 mg / mL. After stirring at 37°C and 50 rpm for 24 h, the Ca content in the solution was determined by inductively coupled plasma mass spectrometry. 2+ content, evaluate the Ca content of nanocarriers 2+ Release pH sensitivity. Experimental results are as follows Figure 7 The experimental results show that the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 can efficiently release Ca in acidic solution. 2+ , to achieve the functions of acidity regulation and disruption of intracellular calcium ion homeostasis in the tumor microenvironment.
[0068] The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 were subjected to intracellular Ca 2+ Sedimentation investigation. MCF-7 / ADR cells in the logarithmic growth phase were seeded in 20 mm glass-bottom culture dishes and cultured for 24 h. They were then incubated with calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles for another 4 h. Fluo-3 AM (a Ca 2+ After incubation with fluorescent probes for 30 min, the cell nuclei were stained with Hoechst 33258 dye, and sections were prepared. The intracellular Ca 2+ Deposition in MCF-7 / ADR tumor cells. Figure 8 The experimental results show that the Ca in calcium carbonate coated mesoporous Prussian blue lipid nanoparticles 2+ It can be efficiently deposited in MCF-7 / ADR cells to achieve the functions of acidity regulation in the tumor microenvironment and disrupting intracellular calcium ion homeostasis.
[0069] The calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 were used to investigate the ROS consumption in tumor cells. MCF-7 / ADR cells in the logarithmic growth phase were inoculated into a 20 mm glass-bottomed culture dish. After culturing for 24 h, PBS (pH 7.4) and calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles (0.1 mg / mL) were incubated with the cells for 4 h respectively; thereafter, the cells were incubated with 2,7-dichlorofluorescein diacetate (DCFH-DA, a universal oxidative stress indicator) for 20 min; finally, the cell nuclei were stained with Hoechst 33258 dye, and sections were prepared. The ROS content in the cells was investigated by laser confocal microscopy. The experimental results are shown in Figure 2. Figure 9 The experimental results showed that compared with the PBS group, the DCFH-DA fluorescence intensity in the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticle group was significantly reduced. This is because the mesoporous Prussian blue in the nanoparticles can exert peroxidase-like activity, catalyzing H2O2 into O2 and H2O, thereby alleviating cellular hypoxia in the tumor microenvironment.
[0070] The in vivo targeting of the calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles prepared in Example 1 was investigated. A mouse subcutaneous tumor model was established with MCF-7 / ADR cells. When the tumor-bearing mice reached a volume of 70-100 mm 3 At 12, 24, and 48 hours after administration, Dir-labeled calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles (Dir: 50 μg / mouse) were injected into the tail vein, and the accumulation of Dir-labeled nanoparticles in the tumor site was observed using a small animal in vivo imaging system (NIFR). Figure 10 The experimental results show that calcium carbonate-coated mesoporous Prussian blue lipid nanoparticles can efficiently accumulate in the tumor sites of tumor-bearing mice, thereby providing the possibility of achieving multi-effect synergistic and integrated tumor inhibition.
[0071] Example 2
[0072] The difference between Example 2 and Example 1 is that the amount of calcium chloride used in step 3 is different.
[0073] Step 1: Accurately weigh 7.5g of polyvinylpyrrolidone and 0.6g of potassium ferricyanide, respectively, and dissolve them in 100mL of 0.01M HCl solution. Stir at room temperature for 30 minutes to obtain a clear yellow solution. Transfer the solution to a reactor and heat at 80°C for 24 hours. After the reaction, centrifuge the resulting dark blue liquid at 40,000rpm for 15 minutes, discard the supernatant, wash the precipitate three times with deionized water, and freeze-dry to obtain Prussian blue nanoparticles.
[0074] Step 2: Accurately weigh 20 mg of the Prussian blue nanoparticles prepared in step 1 and disperse them in 20 mL of 1 M HCl solution. Add 100 mg of PVPK30 and stir magnetically at room temperature for 3 hours. Then transfer the solution to a reactor and heat at 140°C for 3 hours. After the reaction, centrifuge the obtained dark blue liquid at 40,000 rpm for 15 minutes, discard the supernatant, wash the precipitate with deionized water three times, and freeze-dry to obtain mesoporous Prussian blue nanoparticles.
[0075] Step 3: Dissolve 1 mg of mesoporous Prussian blue nanoparticles (MBNPs) obtained in Step 2, 72 mg of calcium chloride, and 700 mg of polyvinylpyrrolidone K30 in 30 mL of anhydrous ethanol and place in a beaker. Wrap the beaker in tin foil, pierce the foil, and place the beaker and 5 g of dry ammonium bicarbonate in an incubator at 45°C for 12 hours. After the reaction, centrifuge at 40,000 rpm for 15 minutes, discard the supernatant, and wash the precipitate with anhydrous ethanol. Centrifuge at 5,000 rpm for 5 minutes to remove large particles. Freeze-dry to obtain calcium carbonate-coated MBNPs.
[0076] The calcium carbonate coated mesoporous Prussian blue nanoparticles prepared in Example 2 were examined by electron microscopy. The experimental results are as follows: Figure 11 The experimental results show that compared with the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in Example 1, the particle size of the nanoparticles becomes larger and the thickness of the CaCO3 coating is significantly increased, indicating that the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared by gas diffusion based on biomineralization technology can increase the calcium loading by increasing the calcium chloride feed ratio.
[0077] Comparative Example 1
[0078] Calcium carbonate-coated mesoporous Prussian blue nanoparticles are prepared by a chemical coprecipitation method, comprising the following steps:
[0079] Step 1: Accurately weigh 7.5g of polyvinylpyrrolidone and 0.6g of potassium ferricyanide, respectively, and dissolve them in 100mL of 0.01M HCl solution. Stir at room temperature for 30 minutes to obtain a clear yellow solution. Transfer the solution to a reactor and heat at 80°C for 24 hours. After the reaction, centrifuge the resulting dark blue liquid at 40,000rpm for 15 minutes, discard the supernatant, wash the precipitate three times with deionized water, and freeze-dry to obtain Prussian blue nanoparticles.
[0080] Step 2: Accurately weigh 20 mg of the Prussian blue nanoparticles prepared in step 1 and disperse them in 20 mL of 1 M HCl solution. Add 100 mg of PVPK30 and stir magnetically at room temperature for 3 hours. Then transfer the solution to a reactor and heat at 140°C for 3 hours. After the reaction, centrifuge the obtained dark blue liquid at 40,000 rpm for 15 minutes, discard the supernatant, wash the precipitate with deionized water three times, and freeze-dry to obtain mesoporous Prussian blue nanoparticles.
[0081] Step 3: Dissolve 1 mg of mesoporous Prussian blue nanoparticles obtained in step 2, 32 mg of calcium chloride and 700 mg of polyvinylpyrrolidone K30 in 29 mL of anhydrous ethanol and place in a beaker to obtain solution A; weigh 245 mg of sodium carbonate ( CaCl2 :n Na2CO3 =1:8) was dissolved in 1 mL of anhydrous ethanol to obtain solution B. Solution B was slowly added dropwise to solution A and magnetically stirred at room temperature for 10 hours. After the reaction, the mixture was centrifuged at 40,000 rpm for 15 minutes, the supernatant discarded, and the precipitate washed with anhydrous ethanol. The precipitate was centrifuged at 5,000 rpm for 5 minutes to remove large particles, and freeze-dried to obtain calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared by the chemical coprecipitation method.
[0082] The calcium carbonate coated mesoporous Prussian blue nanoparticles liquid prepared in Comparative Example 1 were compared, and the experimental results are shown in FIG. Figure 12 The experimental results show that compared with the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in Example 1, the nanoparticles prepared by the chemical coprecipitation method have a white, milky liquid color, indicating that the mesoporous Prussian blue is completely coated by the calcium carbonate coating. On the other hand, the nanoparticles prepared by the chemical coprecipitation method have a lower transparency, indicating that the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared by the chemical coprecipitation method have larger particle sizes and uneven particle size distribution.
[0083] The calcium carbonate coated mesoporous Prussian blue nanoparticles prepared in Comparative Example 1 were examined by electron microscopy. The experimental results are as follows: Figure 13 The experimental results show that compared with the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in Example 1, the particle size of the nanoparticles is significantly increased, and the thickness of the CaCO3 coating is uneven, and a large amount of it is coated on the surface of the mesoporous Prussian blue. This shows that based on biomineralization technology, the gas diffusion method is used to prepare calcium carbonate-coated mesoporous Prussian blue nanoparticles. Compared with the chemical coprecipitation method, the CaCO3 coating thickness is uniform and the nanoparticle size is more uniform. The thickness and calcium loading of the calcium carbonate coating can be effectively controlled by controlling the ratio of mesoporous Prussian blue to calcium chloride. The control process is simple and easy to operate.
[0084] The present invention prepares mesoporous Prussian blue nanoparticles through a hydrothermal synthesis method and a hydrochloric acid etching method; then, based on a biomineralization technology, calcium carbonate is uniformly coated on the surface of the mesoporous Prussian blue by gas diffusion; the shell-core structure of the mesoporous Prussian blue is mineralized by calcium carbonate, so that the drug loading capacity is greatly improved while having sufficient calcium loading efficiency; the thickness and calcium loading amount of the calcium carbonate coating are regulated by controlling the ratio of the mesoporous Prussian blue to calcium chloride, and the control process is simple and easy to operate; a lipid layer is modified on the surface of the shell-core structure of the mesoporous Prussian blue coated with calcium carbonate by an emulsified solvent volatilization method; the nanoparticles have uniform particle size and good dispersibility and stability; calcium and iron in the nanoparticles are both essential trace elements for the human body, and no other heavy metal ions are involved, thereby greatly improving the biocompatibility of the nanoparticles.
[0085] The embodiments provided above are not intended to limit the scope of the present invention, nor are the steps described to limit their execution order. Any obvious improvements to the present invention made by those skilled in the art in combination with existing common knowledge shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing calcium carbonate biomineralized Prussian blue lipid nanoparticles, characterized in that: The following steps are involved: (1) Potassium ferrocyanide and polyvinyl pyrrolidone are dissolved in a hydrochloric acid solution and stirred at room temperature to obtain a clear yellow solution; the yellow solution is transferred to a reaction kettle and heated at a constant temperature of 80° C. for 24 hours. After the reaction is completed, the obtained dark blue liquid is centrifuged at high speed, the supernatant is discarded, the precipitate is washed with deionized water for multiple times, and the Prussian blue nanoparticles are obtained after freeze-drying; (2) dissolving the Prussian blue nanoparticles obtained in step (1) and polyvinyl pyrrolidone in a hydrochloric acid solution, stirring at room temperature for 3 h, transferring the mixed solution to a reaction kettle, and heating at 140° C. for 3 h; after the reaction, centrifuging the obtained dark blue liquid at high speed, discarding the supernatant, washing the precipitate with deionized water for multiple times, and freeze-drying to obtain mesoporous Prussian blue nanoparticles; (3) taking the mesoporous Prussian blue nanoparticles obtained in step (2), dissolving the mesoporous Prussian blue nanoparticles, calcium chloride and polyvinyl pyrrolidone in an organic solvent and placing the mixture in a beaker; wrapping the beaker with tin foil, piercing the beaker, placing the beaker and dry ammonium bicarbonate in a constant temperature box at 45° C., reacting for 12 h, and after the reaction is completed, centrifuging at high speed, discarding the supernatant, washing the precipitate with an organic solvent, centrifuging at low speed to remove large particles in the system, and freeze-drying to obtain calcium carbonate-coated mesoporous Prussian blue nanoparticles; (4) dissolving lecithin, cholesterol, and distearoylphosphatidylethanolamine-polyethylene glycol in a mixed organic solvent to prepare liquid A; dispersing the calcium carbonate-coated mesoporous Prussian blue nanoparticles prepared in step (3) in deionized water to obtain liquid B; mixing liquid A and liquid B in a volume ratio of 1:5, performing intermittent ultrasonication with an ice bath to form an oil-in-water emulsion, removing the organic solvent by rotary evaporation, and filtering with an organic filter membrane to obtain calcium carbonate biomineralized-coated Prussian blue lipid nanoparticles.
2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the hydrochloric acid solution is 0.1-1M, the mass concentration of potassium ferrocyanide in the yellow solution is 0.006-0.06 g / mL, and the mass concentration of polyvinyl pyrrolidone is 0.075-0.75 g / mL.
3. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the hydrochloric acid solution is 1-2 M, the mass concentration of Prussian blue nanoparticles in the mixed solution is 0.1-1 mg / mL, and the mass concentration of polyvinyl pyrrolidone is 1-5 mg / mL.
4. The preparation method according to claim 1, characterized in that: In step (3), the organic solvent includes ethanol and / or methanol, the mass ratio of the mesoporous Prussian blue nanoparticles, calcium chloride and polyvinyl pyrrolidone is 1:32-72:700, and the amount of ammonium bicarbonate is 1-5g.
5. The preparation method according to claim 1, characterized in that: The rotation speed of the high-speed centrifugation in steps (1) to (3) is 15000-40000 rpm, the centrifugation time is 0.25-1h, the freeze-drying temperature is -80°C, the time is 24-48h, and the rotation speed of the low-speed centrifugation in step (3) is 3000-5000 rpm, and the centrifugation time is 5-15min.
6. The preparation method according to claim 1, characterized in that: In step (4), in the liquid A, the mass ratio of lecithin, cholesterol, and distearoylphosphatidylethanolamine-polyethylene glycol in the mixed organic solvent is 2:1:1, the concentration of the lecithin is 1-3 mg / mL, and the molecular weight range of the distearoylphosphatidylethanolamine-polyethylene glycol is 2000-5000.
7. The preparation method according to claim 1, characterized in that: In step (4), the mixed organic solvent is a mixed solvent of chloroform and / or dichloromethane and alcohol, the alcohol includes methanol and / or ethanol, and the mass ratio of chloroform and / or dichloromethane to alcohol is 2:
1.
8. The preparation method according to claim 1, characterized in that: In step (4), in the B solution, the mass concentration of calcium carbonate-coated mesoporous Prussian blue nanoparticles is 1-5 mg / mL, the rotary evaporation temperature is 45-60° C., the organic filter membrane is cellulose diacetate, and the pore size is 0.45 μm. 9 . Calcium carbonate biomineralized Prussian blue lipid nanoparticles prepared according to the preparation method of any one of claims 1 to 8 .
10. Use of the calcium carbonate biomineralized Prussian blue lipid nanoparticles coated according to claim 9 in the preparation of anti-tumor drugs.